Natural History of Incident and Persistent Cutaneous Human Papillomavirus and Human Polyomavirus Infections . (12th January 2022) - Amorrortu, Rossybelle P; Zhao, Yayi; Fenske, Neil A; Cherpelis, Basil S; Messina, Jane L; Giuliano, Anna R; Sondak, Vernon K; Schell, Michael J; Mckay-Chopin, Sandrine; Gheit, Tarik; Waterboer, Tim; Tommasino, Massimo; et al.
Abstract: Background: Cutaneous human papillomaviruses (cuHPV) and polyomaviruses (HPyV) have been implicated in skin cancers; however, interpretation of findings across studies is complicated by limited understanding of the natural history of these infections across normal tissue types. Methods: In total, 675 eyebrow hair (EBH) and skin swab (SSW) samples were collected from 71 skin cancer screening patients every 6 months over 2 years and measured for presence of β-HPV, γ-HPV, and HPyV. Incidence, persistence, and clearance of cuHPV/HPyV were estimated, and risk factors associated with infection were examined. Results: Prevalence, incidence, and persistence of β-HPV, γ-HPV, and HPyV were consistently higher in SSW than in EBH, with types 5, 24, 49, 76 and Merkel cell polyomavirus (MCPyV) having incidence rates greater than 20 per 1000 person-months. Prevalent γ-HPV EBH infections persisted more often in women ( P = .024), incident β-HPV EBH infections persisted less often among individuals with history of blistering sunburn ( P = .019), and prevalent MCPyV SSW infections persisted more often in those with a history of skin cancer ( P = .033). Conclusions: Incidence and persistence of cuHPV/HPyV were observed in SSW and EBH; however, none of the risk factors examined were commonly associated with cuHPV/HPyV infections across normal tissue types. Abstract : Cutaneous human papillomavirus and polyomavirus infection incidence and persistence were consistently higher in skin swabs than in eyebrow hairs. Our findings suggest that the normal tissue type of the infection may play a role in the viral natural history.